Ionospheric Electron Heating Associated With Pulsating Auroras: Joint Optical and PFISR Observations. Issue 5 (31st May 2018) - Liang, Jun; Donovan, E.; Reimer, A.; Hampton, D.; Zou, S.; Varney, R.
Abstract: In a recent study, Liang et al. (2017, https://doi.org/10.1002/2017JA024127 ) repeatedly identified strong electron temperature ( T e ) enhancements when Swarm satellites traversed pulsating auroral patches. In this study, we use joint optical and Poker Flat Incoherent Scatter Radar (PFISR) observations to further investigate the F region plasma signatures related to pulsating auroras. On 19 March 2015 night, which contained multiple intervals of pulsating auroral activities, we identify a statistical trend, albeit not a one‐to‐one correspondence, of strong T e enhancements ( 500–1000 K) in the upper F region ionosphere during the passages of pulsating auroras over PFISR. On the other hand, there is no discernible and repeatable density enhancement in the upper F region during pulsating auroral intervals. Collocated optical and NOAA satellite observations suggest that the pulsating auroras are composed of energetic electron precipitation with characteristic energy >10 keV, which is inefficient in electron heating in the upper F region. Based upon PFISR observations and simulations from Liang et al. (2017) model, we propose that thermal conduction from the topside ionosphere, which is heated by precipitating low‐energy electrons, offers the most likely explanation for the observed electron heating in the upper F region associated with pulsating auroras. Such a heating mechanism is similar to that underlying the "stable auroral red arcs" in the subauroral ionosphere. Our proposal conforms to the notion on the coexistence of an enhanced cold plasma population and the energetic electron precipitation, in magnetospheric flux tubes threading the pulsating auroral patch. In addition, we find a trend of enhanced ion upflows during pulsating auroral intervals. Key Points: Using PFISR observations, we identify strong T e enhancements in the upper F region ionosphere associated with pulsating auroras Heat flux from the topside ionosphere likely account for the observed T e enhancement in the upper F region associated with pulsating auroras Pulsating auroral activity may potentially serve as a driver of the ion outflows in the nightside auroral ionosphere